2021
DOI: 10.21203/rs.3.rs-688703/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of Postnatal Depression in the Slums Nairobi, Kenya: A Cross-Sectional Study

Abstract: BackgroundPostnatal depression (PND) is a universal mental health problem that prevents mothers' optimal existence and mothering. Although research has shown high PND prevalence rates in Africa, including Kenya, little research has been conducted to determine the contributing factors, especially in low-resource communities.ObjectiveThis study aimed to investigate the PND risk factors among mothers attending Maternal and Child Health Clinics (MCH) in the slums, Nairobi.MethodsThis study is cross-sectional, whic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
3
0
0
Order By: Relevance
“…The findings concur with those of Kariuki [29] who indicated that when the process of collection policy is done in a better way, it is crucial in the financial performance of the firm of which logistics companies are part of. The findings also concur with those of Abdi [30] concluded that Information technology is important in the performance of organizations in the logistics sector.…”
Section: 184supporting
confidence: 89%
“…The findings concur with those of Kariuki [29] who indicated that when the process of collection policy is done in a better way, it is crucial in the financial performance of the firm of which logistics companies are part of. The findings also concur with those of Abdi [30] concluded that Information technology is important in the performance of organizations in the logistics sector.…”
Section: 184supporting
confidence: 89%
“…Accordingly, the odds of having postpartum depression was 2.72 times higher among women aged ≤ 24 years compared with those women aged ≥ 35 years old. This finding was supported by the study conducted in Southwest Ethiopia [ 23 ], Sudan [ 33 ], Kenya [ 49 ], and Armenia [ 32 ]. The possible explanation might be due to the fact that younger women are expected to be exposed to emotional distress as they experience childbirth for the first time.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, the odds of experiencing PPD among respondents who had unplanned pregnancy was 3 times more compared with those women who had planned pregnancy. This result is supported by studies conducted in Ethiopia such as Bahir Dar [21], Nekemte town [22], Bench Maji zone, [23], and southwest Ethiopia [26], in Kenya [49], in Nepal [56], and in Pennsylvania [57]. This could be due to the fact that pregnancy itself needs physiological, psychological, and financial preparation.…”
Section: Plos Onesupporting
confidence: 68%
“…The principal aim of this research is to analyze mutual funds in the specific context of the financial market in Kenya. Kariuki (2014) investigated how macroeconomic factors affected the mutual fund industry's financial performance in Kenya. Five independent variables were investigated in the study: money supply, interest rate, inflation rate, and exchange rate.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Theoretical understanding of the relationship between macroeconomic conditions and mutual fund performances is currently lacking in clarity. While some researchers have found a negative association between exchange rates and the performance of mutual funds (Leyian, 2017;Garg & Srivastava, 2019), others argue for a positive correlation between this macroeconomic factor and mutual fund performance (Kariuki, 2014;Njau, 2013).…”
Section: Introductionmentioning
confidence: 99%